2017
DOI: 10.1371/journal.pone.0188385
|View full text |Cite
|
Sign up to set email alerts
|

Comparative metabolomics profiling of engineered Saccharomyces cerevisiae lead to a strategy that improving β-carotene production by acetate supplementation

Abstract: A comparative metabolomic analysis was conducted on recombinant Saccharomyces cerevisiae strain producing β-carotene and the parent strain cultivated with glucose as carbon source using gas chromatography-mass spectrometry (GC-MS), high performance liquid chromatography-mass spectrometry (HPLC-MS) and ultra-high performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS) based approach. The results showed that most of the central intermediates associated with amino acids, carbohydrates, glycolysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 47 publications
(71 reference statements)
1
11
0
Order By: Relevance
“…For example, the mitochondrial proteins involved in TCA cycle (Sdh1p, Sdh2p Sdh3p, Lsc1p, Lsc2p, Cit2p and Cit3p) and ATP synthesis (Atp7p, Atp17p, Atp19p, Atp20p and Tim11p) were up-regulated. This indicated that the ATP generation system became abnormal due to the β-carotene accumulation, which might lead to ATP deficiency in the YBX-01 strain, as shown in our previous study [30]. The proteins related to lipid metabolism (such as Acc1p, Ino1p and Cyb5p) and ergosterol biosynthetic process (Erg1p, Erg4p, Erg6p, Erg20p, Erg24p, and Erg25p) were simultaneously enriched in YBX-01 strain (Additional file 1: Table S1).…”
Section: Mining Potential Transporters For β-Carotene Effluxsupporting
confidence: 52%
See 1 more Smart Citation
“…For example, the mitochondrial proteins involved in TCA cycle (Sdh1p, Sdh2p Sdh3p, Lsc1p, Lsc2p, Cit2p and Cit3p) and ATP synthesis (Atp7p, Atp17p, Atp19p, Atp20p and Tim11p) were up-regulated. This indicated that the ATP generation system became abnormal due to the β-carotene accumulation, which might lead to ATP deficiency in the YBX-01 strain, as shown in our previous study [30]. The proteins related to lipid metabolism (such as Acc1p, Ino1p and Cyb5p) and ergosterol biosynthetic process (Erg1p, Erg4p, Erg6p, Erg20p, Erg24p, and Erg25p) were simultaneously enriched in YBX-01 strain (Additional file 1: Table S1).…”
Section: Mining Potential Transporters For β-Carotene Effluxsupporting
confidence: 52%
“…Acetate, an abundant and renewable resource, can improve protein secretion by increasing ATP content in Schizosaccharomyces pombe [42]. As a precursor of acetyl-CoA, acetate supplementation leads to an increase in carbon flux of the TCA cycle and promotes the synthesis of ATP [30]. In this study, different concentrations of acetate (5 g/L, 10 g/L, and 15 g/L) was added after 12 h cultivation of YBX-SNQ2, and 10 g/L acetate addition showed the best performance for β-carotene production and efflux.…”
Section: Evaluation Of Atp Supply Strategiesmentioning
confidence: 99%
“…In all organisms, arginine biosynthesis consumes ornithine and glutamine, a main nitrogen carrier, which induces an additional cost for the network, considering its high connectivity with the biosynthesis of other amino acids, pigments and nucleotides. Glutamine, specifically, has been identified as one of the most important contributors to carbon and nitrogen metabolism 40 , and a drastic decrease (e.g., 35% decrease in yeast) 6,7 in its abundance is a common response under nitrogen starvation 2,40,41 . Moreover, the consumption of ornithine fully activates the acetyl cycle, thus adding nitrogen and energy costs by consuming glutamate and ATPs.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolic adaptation has been associated with changes in the production or degradation rates of biomolecules. These profiles are observed in various heterotrophic and photoautotrophic microorganisms, increasing their resistance to stress conditions and nutrients limitation 1,[3][4][5][6][7][8][9][10][11][12] . Depletion of carbon and energy sources directly reduce the synthesis of all biomass precursors since carbon is the backbone of nucleic acids, proteins, lipids, and carbohydrates and all anabolic pathways consume energy.…”
Section: Introductionmentioning
confidence: 99%
“…Most attempts have focused almost exclusively on the genes and regulatory controls of the isoprenoid pathway. Some efforts have also been directed towards increasing the cytosolic pools of the precursor acetyl-CoA by engineering pyruvate dehydrogenase (PDH) bypass [ 4 ], overexpression of alcohol dehydrogenase ( ADH2 ) for increasing acetaldehyde pools, a precursor for acetyl-CoA through production from ethanol [ 5 ], decreasing competition for cytosolic acetyl-CoA in the glyoxylate cycle with malate synthase ( MLS1 ) and citrate synthase ( CIT2 ) gene deletions [ 6 ], and exogenous addition of acetate in the exponential phase [ 7 ]. As increasing acetyl-CoA pools from acetate by acetyl-CoA synthases ( ACS1 , ACS2 ) requires ATP, many metabolic engineering strategies have tried to reduce overall ATP cost by decoupling acetyl-CoA supply from ATP hydrolysis [ 8 11 ].…”
Section: Introductionmentioning
confidence: 99%